Exercise Rehabilitation after Anterior Cruciate Ligament Reconstruction - Keun Ok An (Sapientia Publishing Group, 2017)
OBJECTIVES Exercise rehabilitation after anterior cruciate ligament (ACL) reconstruction has changed dramatically in recent years. In this review, we discuss recent changes in exercise programs related to ACL rehabilitation. METHODS We conducted a literature review of recently published articles related exercise programs after ACL reconstruction. RESULTS The accelerated rehabilitation program, which allows patients to achieve full extension ofthe knee early in the postoperative period, is now a widely practiced rehabilitation program. A prospective study of rehabilitation programs after ACL reconstruction showed that early joint exercises do not interfere with the healing of grafts. Instead, they alleviate pain, thereby reducing the negative impact. Moreover, according to several biomechanical studies, open kinetic chain exercises are potentially disadvantageous to knee stability. There is no evidence that early weight bearing results in weakening of graft distraction or internal fixation compared with delayed weight bearing. CONCLUSIONS In conclusion, prevention of ACL injuries and rehabilitative exercise training can help to achieve optimal exercise performance while avoiding the risk of sports-related injury.